2022
DOI: 10.1021/acsaem.2c01122
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the In Situ Surface Reconstruction of Supercapacitive Bimetallic Ni-Co Oxyphosphide during Electrochemical Activation Using Multivariate Statistical Analyses

Abstract: Electrochemical energy storage (EES) technologies are playing a leading role in the global effort to address the energy challenges. Current EES systems are limited by their energy density, capacity, and cycling stability. Some of those limitations arise from nanoscale phenomena, which are not fully understood or accounted for. Electrochemical activation (ECA), an often-overlooked process, creates more active sites on the electrode material and boosts the activity of the system to achieve a higher storage capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…As for the Ni spectrum, the peaks recorded at 856.2 eV and 878 indicate the presence of Ni 2+ species Ni 2p 3/2 and Ni 2p 1/2 , respectively . Besides, the two peak characteristics of oxidized nickel phosphide (Ni–PO x ) were observed at 873.2 eV (2p 1/2 ) and 856.2 eV (2p 3/2 ) . The manganese spectrum showed that the dominant phase formed is Mn 3+ (2p 3/2 ), as indicated by the peak with the highest intensity at 642.7 eV. , Note that a small peak related to Mn 2+ was also observed after deconvolution at 640 eV, along with the characteristic satellite signal of Mn 2+ at 646.5 eV. , The Fe 2p spectrum showed two peaks at 711.9 and 722 eV, with the peak at 714 eV attributed to the oxidized Fe–P .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As for the Ni spectrum, the peaks recorded at 856.2 eV and 878 indicate the presence of Ni 2+ species Ni 2p 3/2 and Ni 2p 1/2 , respectively . Besides, the two peak characteristics of oxidized nickel phosphide (Ni–PO x ) were observed at 873.2 eV (2p 1/2 ) and 856.2 eV (2p 3/2 ) . The manganese spectrum showed that the dominant phase formed is Mn 3+ (2p 3/2 ), as indicated by the peak with the highest intensity at 642.7 eV. , Note that a small peak related to Mn 2+ was also observed after deconvolution at 640 eV, along with the characteristic satellite signal of Mn 2+ at 646.5 eV. , The Fe 2p spectrum showed two peaks at 711.9 and 722 eV, with the peak at 714 eV attributed to the oxidized Fe–P .…”
Section: Resultsmentioning
confidence: 95%
“…66 Besides, the two peak characteristics of oxidized nickel phosphide (Ni−PO x ) were observed at 873.2 eV (2p 1/2 ) and 856.2 eV (2p 3/2 ). 67 The manganese spectrum showed that the dominant phase formed is Mn 3+ (2p 3/2 ), as indicated by the peak with the highest intensity at 642.7 eV. 68,69 Note that a small peak related to Mn 2+ was also observed after deconvolution at 640 eV, along with the characteristic satellite signal of Mn 2+ at 646.5 eV.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Among these energy storage devices, supercapacitors (SCs) enjoy the merits of superb reversibility, high power output, and very long cycle life. Based on the energy storage mechanism, supercapacitor electrodes can be classified into the following: (1) electrochemical double layer electrodes (EDL) such as carbon-based materials, where the charge is physically stored by electrostatic charge adsorption at the electrode/electrolyte interface; (2) pseudo-capacitive electrodes, which store charges via surface intercalation and diffusion processes; and (3) battery-type electrodes, which involve diffusion and redox reaction processes . Although the performance of supercapacitors is between conventional capacitors (very low energy density) and batteries (low power density), there is still a room to identify and fabricate robust and cheap supercapacitor electrode materials that can deliver high energy density and excellent electrochemical performance . This can be attained by devising a supercapattery, a hybrid device that includes different electrode materials with different charge storage mechanisms, such as combining an EDL electrode with a battery-type electrode. , For battery-type electrodes, materials such as transition metal oxides, hydroxides, nitrides, and sulfides as well as conductive polymers have been extensively investigated as potential candidates. , …”
Section: Introductionmentioning
confidence: 99%
“…9 Although the performance of supercapacitors is between conventional capacitors (very low energy density) and batteries (low power density), there is still a room to identify and fabricate robust and cheap supercapacitor electrode materials that can deliver high energy density and excellent electrochemical performance. 10 This can be attained by devising a supercapattery, a hybrid device that includes different electrode materials with different charge storage mechanisms, such as combining an EDL electrode with a battery-type electrode. 11,12 For battery-type electrodes, materials such as transition metal oxides, hydroxides, nitrides, and sulfides as well as conductive polymers have been extensively investigated as potential candidates.…”
Section: Introductionmentioning
confidence: 99%